Comparative Analysis of Online and Offline Coaching on Development of Basic Understanding Among Students of Ahmedabad City - Prajapati, Nirav; Makwana, Chirag; Vidani, Jignesh (Contemporary Journal of Applied Sciences, 2024)
This study examines the comparative effects of online and offline tutoring on the development of basic understanding among students in Ahmedabad. Using a mixed methods approach, the study analyzes students’ preferences, perceptions, and academic outcomes associated with each tutoring modality. The study identifies significant implications for educational practice, suggesting that a blended approach that combines the strengths of online and offline tutoring can enhance student engagement and learning outcomes. Recommendations for future research include longitudinal studies, mixed methods approaches, and investigations into the impact of technology and teacher training on educational effectiveness. Ultimately, this study contributes to the growing discourse on optimizing learning environments in a rapidly evolving educational landscape